Cellular insights of beech leaf disease reveal abnormal ectopic cell division of symptomatic interveinal leaf areas. - Paulo Vieira; Mihail R Kantor; Andrew Jansen; Zafar A Handoo; Jonathan D Eisenback (PLoS ONE)
The beech leaf disease nematode, Litylenchus crenatae subsp. mccannii, is recognized as a newly emergent nematode species that causes beech leaf disease (BLD) in beech trees (Fagus spp.) in North America. Changes of leaf morphology before emergence from the bud induced by BLD can provoke dramatic effects on the leaf architecture and consequently to tree performance and development. The initial symptoms of BLD appear as dark green, interveinal banding patterns of the leaf. Despite the fast progression of this disease, the cellular mechanisms leading to the formation of such aberrant leaf phenotype remains totally unknown. To understand the cellular basis of BLD, we employed several types of microscopy to provide an exhaustive characterization of nematode-infected buds and leaves. Histological sections revealed a dramatic cell change composition of these nematode-infected tissues. Diseased bud scale cells were typically hypertrophied and showed a high variability of size. Moreover, while altered cell division had no influence on leaf organogenesis, induction of cell proliferation on young leaf primordia led to a dramatic change in cell layer architecture. Hyperplasia and hypertrophy of the different leaf cell layers, coupled with an abnormal proliferation of chloroplasts especially in the mesophyll cell layers, resulted in the typical interveinal leaf banding. These discrepancies in leaf cell structure were depicted by an abnormal rate of cellular division of the leaf interveinal areas infected by the nematode, promoting significant increase of cell size and leaf thickness. The formation of symptomatic BLD leaves is therefore orchestrated by distinct cellular processes, to enhance the value of these feeding sites and to improve their nutrition status for the nematode. Our findings thus uncover relevant cellular events and provide a structural framework to understand this important disease.